Factors Affecting Discharge Disposition after Primary Simultaneous Bilateral Joint Arthroplasty. Issue 3 (October 2019) - Edwards, Danielle; Anderson, Allison; Pleus, Michael R.; Smith, Jerome B.; Nguyen, Joseph T.
Background: Predicting discharge destination following total joint arthroplasty (TJA) is important, as discharge destination has major implications for post-operative costs, clinical outcomes, and readmissions. Few studies have looked at factors affecting discharge destination for patients following primary simultaneous bilateral total joint arthroplasty. Questions/Purposes: The purpose of this study was to describe clinical and social factors that relate to a discharge to home versus rehabilitation facility (RF) for patients after primary simultaneous bilateral total hip arthroplasty (PSBTHA) or primary simultaneous bilateral total knee arthroplasty (PSBTKA). Methods: The inclusion criteria for this retrospective cohort study were all patients after PSBTHA or PSBTKA at a metropolitan orthopedic specialty hospital between February 1, 2016, and March 31, 2018. Exclusion criteria were revisions, differing weight-bearing status, bed-rest orders, and non-standard hip precautions. Social and clinical demographic data were collected. Multiple regression analysis was conducted to determine which factors related most to discharge plan. Results: Of 253 PSBTHA patients, 153 were discharged home and 100 to an RF. Regression analysis found a posterolateral approach to be the only significant factor associated with an RF discharge. Of 619 PSBTKA patients, 136 were discharged home and 483 to RF. Increased body mass index and older age increased the likelihood of discharge to an RF. Patients with an adductor-only nerve block were more likely to be sent to RF. Conclusion: These findings shed light on the variables that contribute to discharge destination after PSBTHA and PSBTKA. Such information allows for safe pre-operative discharge planning and assists with discharge to the appropriate level of patient care. Future studies might investigate the effect of surgeon experience, surgical technique, and pre-operative discussion with a physical therapist on the discharge disposition of patients undergoing bilateral total joint arthroplasty.